THE GALACTIC CALIBRATION OF THE CEPHEID PERIOD-LUMINOSITY RELATION AND ITS IMPLICATIONS FOR THE UNIVERSAL DISTANCE SCALE - Turner, D. G.; Majaess, D. J.; Lane, D. J.; Rosvick, J. M.; Henden, A. A.; Balam, D. D. (Одеські астрономічні публікації, 2010)
The Galactic calibration of the period-luminosity (PL) relation for classical Cepheids is examined using trigonometric, open cluster, and pulsation parallaxes, which help establish independent versions of the relationship. The calibration is important for the continued use of classical Cepheids in constraining cosmological models (by refining estimates for H0), for defining zero-points for the SNe Ia and population II (Type II Cepheids/RR Lyrae variables) distance scales, for clarifying properties of the Milky Way’s spiral structure, and for characterizing dust extinction affecting Cepheids in the Milky Way and other galaxies. Described is a program to extend and refine the Galactic Cepheid PL relation by obtaining UBVRIJHKs photometry and spectra for stars in open clusters suspected of hosting classical Cepheids, using the the facilities of the OAMM, DAO, AAVSO, and ARO.